Development of the HARMONI spectrograph for ESO’s Extremely Large Telescope - Hidalgo Valadez, AA (2023)
HARMONI is the integral field spectrograph (IFS) for the European Southern Observatory's Extremely Large Telescope (ELT). This versatile instrument assisted by adaptive optics will deliver diffraction-limited spectroscopic capabilities across the near-infrared wavelength range, taking full advantage of the ELT's combination of exceptional spatial resolution and vast collecting area to enable groundbreaking scientific research. HARMONI is a unique ground-based astronomical instrument due to its size and the fact that it will be the first IFS to operate on an ELT. Some of HARMONI's technology was already implemented in previous astronomical instruments, but at a smaller scale, lower level of integration complexity, and never for this type of telescope. Consequently, multiple development challenges must be addressed for its successful realization. This thesis addresses two development challenges: implementing a lens mount for HARMONI's spectrograph cameras and evaluating the potential for dielectric mirror coatings to enhance instrument throughput. This thesis proposes a flexure lens mount for HARMONI's spectrograph cameras and demonstrates how it can be implemented to meet the cameras' alignment requirements. The thesis meticulously presents the assembly process and validation of the radial alignment of two lens mount engineering models in a HARMONI-simulated operational environment. Secondly, this thesis demonstrates that dielectric mirrors are a feasible technology for the HARMONI instrument by establishing that broad-spectrum coatings can be designed and manufactured, and by validating four coating types for HARMONI's lifetime and operational conditions. Additionally, the thesis provides transmission estimates, highlighting the substantial throughput improvements achieved by applying dielectric mirror coatings to eligible surfaces.